The feasibility of harmonizing gluten ELISA measurements. (1st November 2017) - Rzychon, Malgorzata; Brohée, Marcel; Cordeiro, Fernando; Haraszi, Reka; Ulberth, Franz; O'Connor, Gavin
Highlights: Different ELISA kits for measuring gluten yield different responses. The differences between pairs of kits can vary by a factor of 20. The current measurement system cannot fully support legislative gluten-free claims. Comparability of measurements is limited by poor correlation between kit results. Lack of correlation creates bias that cannot be removed using reference materials. Abstract: Many publications have highlighted that routine ELISA methods do not give rise to equivalent gluten content measurement results. In this study, we assess this variation between results and its likely impact on the enforcement of the EU gluten-free legislation. This study systematically examines the feasibility of harmonizing gluten ELISA assays by the introduction of: a common extraction procedure; a common calibrator, such as a pure gluten extract and an incurred matrix material. The comparability of measurements is limited by a weak correlation between kit results caused by differences in the selectivity of the methods. This lack of correlation produces bias that cannot be corrected by using reference materials alone. The use of a common calibrator reduced the between-assay variability to some extent, but variation due to differences in selectivity of the assays was unaffected. Consensus on robust markers and their conversion to "gluten content" are required.